Burtas Uterus Involution Phantom Development - Novianti, Lily; Komariah, Nurul; Asmalinda, Wita (Poltekkes Kemenkes Tanjung Karang, 2024)
One way to diagnose retained placenta is by palpating the uterus to confirm uterine involution. Midwives must have these competencies. One effort to improve student competency is the availability of complete facilities and infrastructure. Currently, the phantom used does not describe in detail the process of uterine involution according to postpartum physiology. Detailed and detailed phantoms are very expensive. This research aims to develop a burtas (paper pulp) uterus involution phantom. It is a phantom covering several parts: the pelvis, abdomen, uterus, and external genitalia. The research was done in the laboratory of the Midwifery Department, Health Polytechnic, Ministry of Health, Palembang, June-October 2023. Research Subjects were DIII Midwifery Study Program students by purposive sampling in small groups of ten people and large groups of 20 people. This research uses a development research design known as Research and Development (R&D). Research and development aim to develop an existing product that can be tested for feasibility and effectiveness. The stages are potential and problems, data collection, product design, design validation, design revision, product trials, product revisions, usage trials, product revisions, andÂ production. The burtas uterine involution phantom feasibility test results were declared very feasible by media experts with a score of 100%. Material expert with a score of 100%, Students 88.03%. The developed uterine involution phantom can be used as a phantom or alternative teaching aid for examining uterine involution in midwifery and breastfeeding care practicums.